Quiste poplíteo familiar. - Hernández, Alejandro; Aguirre Negrete, María Guadalupe; Nazara, Zamira; Cantú, José María (Revista Cubana de Pediatría, 2023)
Describe en una familia mexicana el segundo informe de quiste poplíteo familiar.